The Simms Collection of Plains Cree material culture from southeastern Saskatchewan / Fieldiana, Anthropology, new series, no.6 - VanStone, James W. (Chicago, Ill. : Field Museum of Natural History, 1983)
Bibliography: p. 24. Fieldiana series has been published as Anthropological Series by Field Columbian Museum (1895-1909) and Field Museum of Natural History (1909-1943), and as Fieldiana: Anthropology by Chicago Natural History Museum (1945-1966) and Field Museum of Natural History (1966-).